Meningkatkan Hasil Belajar Siswa SD Al-Irsyad Melalui LKPD Berbasis Realistic Mathematics Education pada Materi Statistika - Permatasari, Intan; Budi Lestari, Andika Setyo; Fuat, Fuat (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2024)
Abstract The teaching of statistics in elementary schools, which tends to be conventional, can result in students not fully understanding the concepts of data collection and presentation. Improving students' problem-solving skills can be achieved by developing Student Worksheets (LKPD) in statistics based on the Realistic Mathematics Education (RME) approach. This research aims to measure the effectiveness of using LKPD based on Realistic Mathematics Education (RME) in enhancing students' learning outcomes in statistics. This study uses a quasi-experimental method with a one-group pretest-posttest model. The research involves sixth-grade students from Al Irsyad Elementary School using research instruments that consist of interviews, questionnaires, and tests, including pretests and posttests. Based on the pretest results, the average score was 50,83. Meanwhile, the posttest results increased to 86,67. The N-Gain calculation showed an average improvement in student learning outcomes reaching 0,728, which falls into the high category with a mastery percentage of 91,67%. This indicates that the Realistic Mathematics Education (RME)-based LKPD is effective in enhancing students' mathematical understanding